IIOld English. Issue 1 (28th September 2022) - Burns, Rachel A; Kehoe, Niamh; Knowles, Emma; Pascual, Rafael J; Ponirakis, Eleni; Tedford, Margaret
Abstract: This chapter has ten sections: 1. Manuscript Studies; 2. Cultural and Intellectual Contexts; 3. Literature: General; 4. The Poems of the Exeter Book; 5. The Poems of the Vercelli Book; 6. The Poems of the Junius Manuscript; 7. Beowulf and the Beowulf Manuscript; 8. Other Poems; 9. Prose; 10. Reception. Section 1 is by Rachel A. Burns; sections 2 and 9 are by Margaret Tedford; section 3 is by Margaret Tedford with contributions by Rachel A. Burns; section 4 is by Niamh Kehoe; sections 5 and 7 are by Rafael J. Pascual; section 6 is by Emma Knowles; sections 8 and 10 are by Eleni Ponirakis.